High-frequency trading and price informativeness - Jasmin Gider; Simon Schmickler; Christian Westheide (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
We study how stock price informativeness changes with the presence of highfrequency trading (HFT). Our estimate is based on the staggered start of HFT participation in a panel of international exchanges. With HFT presence market prices are a less reliable predictor of future cash ows and investment, even more so for longer horizons. Further, idiosyncratic volatility decreases, mutual funds trade less actively and their holdings deviate less from the market-capitalization weighted portfolio. These findings suggest that price informativeness declines with HFT presence, consistent with theoretical models of HFTs' ability to anticipate informed order ow, reducing incentives to acquire fundamental information.
Keywords: G10; G14; 330; High-Frequency Trading; Price Efficiency; Information Acquisition; Information Production